Predictors of symptom persistence and respiratory sequelae in respiratory symptomatics presenting to a post-COVID clinic - Athulya S Kumar; Venugopal KP; Sajitha M; John Sonia (Asian Journal of Medical Sciences, 2023)
Background: COVID-19 infection causes the persistence of respiratory symptoms and functional impairment, which require prolonged follow-up care. Identification of individuals at risk for respiratory sequelae helps in optimal follow-up and early identification of complications. Aims and Objectives: The present study aims to find the clinical profile, predictors of respiratory symptom persistence, and functional impairment in post-COVID patients. Materials and Methods: Prospective observational study was done on patients who attended the post-COVID clinic in the pulmonary medicine outpatient department (OPD) in a tertiary care center in central Kerala from June 2021 to August 2021 with persisting respiratory symptoms after becoming COVID-19 negative and evaluated with a proforma regarding clinical history and symptoms. Patients were followed up at one and 3 months. Clinical, functional, and radiological factors were assessed. They were reassessed at 3 months. Spirometry was done in those with persistent symptoms at 3 months. High-resolution computed tomography (CT) was performed in those with significant desaturation on 6-min walk test (6MWT). Results: Of 348 patients, 6 died, 4 lost follow-up, 12 patients had alternative diagnoses during the study period. About 29.4% were symptomatic at 3 months. CT severity score improved over 3 months and the proportion of patients with exercise-induced desaturation in 6MWT decreased over 3 months. All patients showed a restrictive abnormality except two. A significant association was found between the persistence of symptoms at 3 months and type 2 diabetes mellitus, severe illness during the initial phase, persistent elevation of inflammatory markers, and increased radiological involvement. Alternative diagnosis and treatment-related complication was seen in 12 patients, which included infections such as tuberculosis, nocardia and fungal infection, malignancy, CTEPH, and post-intubation tracheal stenosis. Conclusion: A minor group of severe COVID-19 pneumonia survivors have delayed resolution of symptoms with functional impairment. Improvement in spirometry lags behind clinical and radiological improvement.